iPad for seniors - Spivey, Dwight (--For dummies., 2025)
"Presents an up-to-date and straightforward guide for anyone who wants to know how to use one of Apple's famous tablets without all the muss, fuss, and jargon of more complicated resources. In this book, you'll find easy-to-read type, crisp figures and illustrations, and down-to-earth instructions that show you exactly how to get set up, customize your device, connect to the web, chat with your friends and family, listen to music, watch videos, download apps, and much more. You'll learn how to secure your tablet, so your data and privacy remain safe. You'll also discover how you can use your iPad to get organized, plan your schedule, and even connect to your home Wi-Fi"--